Socio-spatialities of vulnerability: towards a polymorphic perspective in vulnerability research - Etzold, Benjamin; Sakdapolrak, Patrick (DIE ERDE – Journal of the Geographical Society of Berlin, 2016)
“The space of vulnerability” – the title of the influential paper by Michael Watts and Hans-Georg Bohle from 1993 highlights the importance of spatiality for vulnerability research. As geographers have fundamentally shaped the concept of vulnerability, the issue of spatiality has been crucial for vulnerability from the outset. However, what notion of space have scholars adopted in their vulnerability analysis? The aim of the paper is to assess the ways in which space has been conceptualised in vulnerability research. We conduct this assessment behind the background of the conceptual development of space in human geography. Of particular interest is the question of how the successive socio-spatial turns identified by Jessop et al. (2008), which evolved around the categories of place, scale, network and territory, are reflected in publications on vulnerability. The assessment is based on a review of literature. We found that all four key socio-spatial categories have been taken up by scholars for vulnerability analysis. Following Jessop et al. we argue that a critical geography of vulnerability should acknowledge the polymorphy of socio-spatialities and assess the interplay of place, network, scale, and territory in the (re)production of vulnerability. We exemplify the argument with case studies from Bangladesh and Thailand and conclude that the full repertoire of spatial and social theories are needed in order to fully understand the social and spatial (re)production of vulnerability.